The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/1746-1596-5-24
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction and placental angiogenesis

Abstract: BackgroundVascular endothelial growth factor (VEGF), basic-fibroblast growth factor (b-FGF), and endothelial nitric oxide synthase (eNOS) are factors that take part in placental angiogenesis. They are highly expressed during embryonic and fetal development, especially in the first trimester. In this study, we aimed to investigate the role of placental angiogenesis in the development of intrauterine growth restriction (IUGR) by comparing the levels of expression of VEGF-A, b-FGF, and eNOS in normal-term pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
94
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 20 publications
8
94
0
7
Order By: Relevance
“…Defects in placental vascular development can cause embryonic death and abnormal organogenesis, can negatively affect fetal growth and can confer a higher risk of disease in the postnatal life (Barker et al, 1989). For example, defective patterning of the fetoplacental vasculature, also known as the labyrinth, results in abnormal heart development in mouse (Shaut et al, 2008) and human (Demicheva and Crispi, 2014), and causes intrauterine growth restriction (IUGR) (Barut et al, 2010). IUGR affects up to 32% of pregnancies in some developing countries (Ananth and Vintzileos, 2009), and can cause cardiovascular disease in utero and in adulthood (Demicheva and Crispi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in placental vascular development can cause embryonic death and abnormal organogenesis, can negatively affect fetal growth and can confer a higher risk of disease in the postnatal life (Barker et al, 1989). For example, defective patterning of the fetoplacental vasculature, also known as the labyrinth, results in abnormal heart development in mouse (Shaut et al, 2008) and human (Demicheva and Crispi, 2014), and causes intrauterine growth restriction (IUGR) (Barut et al, 2010). IUGR affects up to 32% of pregnancies in some developing countries (Ananth and Vintzileos, 2009), and can cause cardiovascular disease in utero and in adulthood (Demicheva and Crispi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in vitro studies showed that IUGR placental villous stromal cells altered ability to stimulate endothelial tubule-like structure formation and migration [37]. In addition, the imbalance between pro-and antiangiogenic factors is well documented in placentas and in maternal blood of IUGR and PE pregnancies, suggesting a role in their pathophysiology [38,39]. Endothelial progenitors contribute to tissue regeneration by induction of new vessels, thereby increasing tissue perfusion and oxygenation [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Any alteration of capillaries in terminal villi has straight effect on fetomaternal transfusion, fetal growth and development [5]. Development of fetus could be disturbed by placental insufficiency that can result to low birth weight, premature infants, and increased perinatal mortality and morbidity [6][7][8][9]. Placental size and microvessels' quantity increase up to the end of the pregnancy as fetal nutrients requirements increase with gestational duration [1,10].…”
Section: Introductionmentioning
confidence: 99%